1998
DOI: 10.1093/treephys/18.12.795
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimates of uptake and internal cycling of 14N-labeled fertilizer in mature walnut trees

Abstract: Uptake and internal cycling of nitrogen (N) in mature walnut trees was studied over a period of 6 years using (15)N-depleted fertilizer and full-canopied walnut (Juglans regia L. cv Hartley) trees. The magnitude of internal N cycling, i.e., the availability of N for new growth from internal N pools, was quantified using both the percent annual depletion (PAD) and the N balance budget approaches. There was good agreement between the two measures, and about 60% of annual N demand was derived from N redistributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 18 publications
5
46
0
Order By: Relevance
“…When shoot growth was completed, N remobilization had provided around 54% of total N to new shoots. This result is consistent with the values of 60% estimated for larger walnut trees grown in the orchard by Weinbaum and Van Kessel (1998), although higher values of 75% have also been reported for field-growing walnut trees by Deng et al (1989). Similar percentages of N derived from remobilization for new growth were found in young pear (Pyrus communis) trees (Taglivani et al, 1997), in kiwifruit (Actinidia deliciosa) in orchard conditions (Ledgard and Smith, 1992), and in B. pendula, 40% (Millard et al, 1998).…”
Section: Importance Of N Remobilization For Spring Growth In Walnutsupporting
confidence: 87%
See 2 more Smart Citations
“…When shoot growth was completed, N remobilization had provided around 54% of total N to new shoots. This result is consistent with the values of 60% estimated for larger walnut trees grown in the orchard by Weinbaum and Van Kessel (1998), although higher values of 75% have also been reported for field-growing walnut trees by Deng et al (1989). Similar percentages of N derived from remobilization for new growth were found in young pear (Pyrus communis) trees (Taglivani et al, 1997), in kiwifruit (Actinidia deliciosa) in orchard conditions (Ledgard and Smith, 1992), and in B. pendula, 40% (Millard et al, 1998).…”
Section: Importance Of N Remobilization For Spring Growth In Walnutsupporting
confidence: 87%
“…A second hypothesis is that the amino acids were specific to N remobilization, but that remobilization of N taken up in 1999 (hence labeled N) and in 1998 (hence unlabeled N) occurred concurrently. The latter hypothesis is supported by the fact that Weinbaum and Van Kessel (1998) demonstrated that N assimilated in a given year can be remobilized 2 years later in walnut. In this case, changes in APE during the 80 d after bud burst could be attributable to changes in the relative importance of remobilization from labeled N taken up in 1999 and unlabeled N taken up in 1998.…”
Section: Toward a New Methods For Assessing N Remobilization?mentioning
confidence: 87%
See 1 more Smart Citation
“…More recently, Boaretto et al ( 2010 ) estimated the NUpE averaged in 36% and 52% for orange and lemon trees (3 years old), respectively, both grafted on Swingle citrumelo. Similar values ranging between 25% and 80% were obtained not lately in mature trees grown in the fi eld (Dasberg et al 1984 ; Feigenbaum et al 1987 ;Weinbaum and Van Kessel 1998 ) and citrus rootstock seedlings (Lea-Cox and Syvertsen 1996 ) . The young nonbearing citrus plant, conversely, exhibited lower values of FUE by <5% (Weinert et al 2002 ) and <6% (Menino et al 2007 ) in the fi rst year after transplantation, while Lea-Cox et al ( 2001 ) reported FNR values ranging from 14.9% to 39.3% in bearing Redblush grapefruit, 4 years old.…”
Section: Nitrogen Use Ef Fi Ciency De Fi Nitionssupporting
confidence: 65%
“…roots and stem) served as N stores for spring growth in deciduous trees, e.g. Betula pendula [10], Juglans regia [19] or Prunus persica [14]. Marmann et al [8] showed that in Fraxinus excelsior N was mainly stored in the roots, whereas our data indicate that in beech N stocks in coarse roots and stem contributed about the same portion to new shoot growth.…”
Section: Resultsmentioning
confidence: 70%